Role of TRP ion channels in cerebral circulation and neurovascular communication. (20th November 2021) - Kuppusamy, Maniselvan; Ottolini, Matteo; Sonkusare, Swapnil K.
Highlights: Overview of neurovascular communication and blood brain barrier function. Biophysical properties and roles of individual TRP channels involved in neurovascular communication. Conclusions and Future Research Directions. Abstract: The dynamic regulation of blood flow is essential for meeting the high metabolic demands of the brain and maintaining brain function. Cerebral blood flow is regulated primarily by 1) the intrinsic mechanisms that determine vascular contractility and 2) signals from neurons and astrocytes that alter vascular contractility. Stimuli from neurons and astrocytes can also initiate a signaling cascade in the brain capillary endothelium to increase regional blood flow. Recent studies provide evidence that TRP channels in endothelial cells, smooth muscle cells, neurons, astrocytes, and perivascular nerves control cerebrovascular contractility and cerebral blood flow. TRP channels exert their functional effects either through cell membrane depolarization or by serving as a Ca 2+ influx pathway. Endothelial cells and astrocytes also maintain the integrity of the blood-brain barrier. Both endothelial cells and astrocytes express TRP channels, and an increase in endothelial TRP channel activity has been linked with a disrupted endothelial barrier function. Therefore, TRP channels can play a potentially important role in regulating blood-brain barrier integrity. Here, we review the regulation of cerebrovascular contractility by TRP channels under healthy and disease conditions and their potential roles in maintaining blood-brain barrier function.